Long-Lasting Unruptured Large Intracranial Aneurysm in Bilateral Moyamoya Disease: Case Report - Eunyoung Chae; Soomin Jeong; Chan-Hyuk Lee (Case Reports in Neurological Medicine)
Introduction. The rupture risk of intracranial aneurysms in patients with moyamoya disease is higher than that in the general population. We report a confirmed case of moyamoya disease with bilateral middle cerebral artery (MCA) occlusion with a large and long-lasting aneurysm. Case. A 71-year-old woman visited the clinic with a large intracranial aneurysm. The patient was diagnosed with an ischemic stroke 2 months ago. She exhibited weakness in the left upper and lower extremities and dysarthria and was taking aspirin. The brain magnetic resonance imaging showed complete occlusion in the bilateral MCA proximal (M1) and a large 11 × 11 mm nonruptured cerebral aneurysm in the A3 segment of the left anterior cerebral artery. On transfemoral cerebral angiography, the patient was diagnosed with Suzuki grade VI moyamoya disease with bilateral MCA occlusion. After 7 years, the cerebral aneurysm size further increased, but it remained unruptured. Conclusions. Here, the patient had moyamoya disease with a large aneurysm, but aneurysmal rupture did not occur even after 7 years. Our case report might help in understanding the mechanisms of cerebral aneurysm occurrence and rupture in moyamoya patients.